Prove (SinØ+cosø)(tanø+cotø)=secø+cosecø
Answers
Answered by
3
To prove----->
(Sinφ + Cosφ) (tanφ + Cotφ) = Secφ + Cosecφ
To prove-----> LHS
= ( Sinφ + Cosφ ) ( tanφ + Cotφ )
We know that,
tanφ = Sinφ / Cosφ , Cotφ = Cosφ / Sinφ , applying it we get,
= ( Sinφ + Cosφ ) ( Sinφ/Cosφ + Cosφ/Sinφ )
= ( Sinφ + Cosφ ) { ( Sin²φ + Cos²φ ) / Sinφ Cosφ }
We know that,
Sin²θ + Cos²θ = 1 , applying it we get,
= ( Sinφ + Cosφ ) ( 1 / Sinφ Cosφ )
= ( Sinφ + Cosφ ) / Sinφ Cosφ
= Sinφ / Sinφ Cosφ + Cosφ / Sinφ Cosφ
= 1 / Cosφ + 1 / Sinφ
We know that,
Secθ = 1 / Cosθ , Cosecθ = 1 / Sinθ , applying it , we get,
= Secφ + Cosecφ = RHS
Similar questions